Radiation therapy for the solitary plasmacytoma - Esengül Koçak; Giorgio Ballerini; Abderrahim Zouhair; Mahmut Özşahin (Turkish Journal of Hematology, 2010)
Plasma-cell neoplasms are classically categorized into four groups as: multiple myeloma (MM), plasma-cell leukemias, solitary plasmacytomas (SP) of the bone (SPB), and extramedullary plasmacytomas (EMP). These tumors may be described as localized or diffuse in presentation. Localized plasma-cell neoplasms are rare, and include SP of the skeletal system, accounting for 2-5% of all plasma-cell neoplasms, and EMP of soft tissue, accounting for approximately 3% of all such neoplasms. SP is defined as a solitary mass of neoplastic plasma cells either in the bone marrow or in various soft tissue sites. There appears to be a continuum in which SP often progresses to MM. The main treatment modality for SP is radiation therapy (RT). However, there are no conclusive data in the literature on the optimal RT dose for SP. This review describes the interrelationship of plasma-cell neoplasms, and attempts to determine the minimal RT dose required to obtain local control.